Effect of a behaviour change intervention on the quality of peri-urban sanitation in Lusaka, Zambia: a randomised controlled trial. Issue 4 (April 2019) - Tidwell, James B; Chipungu, Jenala; Bosomprah, Samuel; Aunger, Robert; Curtis, Val; Chilengi, Roma
Summary: Background: Poor sanitation in peri-urban areas is a growing public health problem. We tested a scalable, demand-side behaviour change intervention to motivate landlords to improve the quality of shared toilets within their plots. Methods: We did a residential plot-randomised controlled trial in a peri-urban community in Lusaka, Zambia. We enrolled adult resident landlords on plots where at least one tenant lived. We allocated landlords 1:1 to intervention and control arms on the basis of a random number sequence. The intervention was developed using the Behaviour Centred Design approach and consisted of a series of group meetings designed to motivate sanitation quality improvement as a way to build wealth and reduce on-plot conflict; no subsidies or materials were provided. The control group received no intervention. The four primary outcomes were having a rotational cleaning system in place (to improve hygiene); having a solid door on the toilet used by tenants with an inside lock (for privacy); having an outside lock (for security); and having a sealed toilet (to reduce smell and contamination). We measured outcomes 1 month before the start of the intervention and 4 months after the end of the intervention. Data collectors measuring outcomes were blinded to group assignment. We analysed outcomes by intention to treat, including all landlords with study-end results. Because the outcomes were assumed to not be independent, we used a family-wise error rate of 0·05 to calculate an adjusted significance level of 0·0253. This study was registered withClinicalTrials.gov, numberNCT03174015 . Findings: Between June 9 and July 6, 2017, 1085 landlords were enrolled and randomly assigned to the intervention (n=543) or the control group (n=542). The intervention was delivered from Aug 1, 2017, and evaluated from Feb 15 to March 5, 2018. Analysis was based on the 474 intervention and 454 control landlords surveyed at study end. The intervention was associated with improvements in the prevalence of cleaning rotas (relative risk 1·16, 95% CI 1·05–1·30; p=0·0011), inside locks (1·34, 1·10–1·64; p=0·00081), outside locks (1·27, 1·06–1·52; p=0·0028), and toilets with simple covers or water seals (1·25, 1·04–1·50; p=0·0063). Interpretation: It is possible to improve the structural quality and cleanliness of shared sanitation by targeting landlords with a scalable, theory-driven behaviour change intervention without subsidy or provision of the relevant infrastructure. Funding: Sanitation and Hygiene Applied Research for Equity.